Comparison of Freehand 3D and 4D Ultrasound to Measure Thrombus Volume in Patients with Acute Deep Vein Thrombosis. Issue 2 (June 2016) - Zhao, Limin; Patel, Richa; Sikdar, Siddhartha; Prior, Steven J.
Objectives: Current imaging techniques have limited ability to quantify thrombus burden in patients with acute deep vein thrombosis (DVT). There is limited ability to objectively measure clot progression or clot resolution over time and with treatment. These critical measures are important determinants of optimal treatment and therapeutic success for thrombolysis or thrombectomy treatment of DVT. In this study, we evaluated the feasibility and reliability of a method of quantifying thrombus volume using freehand three-dimensional (3D) ultrasonography and compared it to a commercially available four-dimensional (4D) transducer for acquiring and analyzing 3D ultrasound images to measure thrombus volume. Methods: We studied 10 consecutive patients with a first episode of acute DVT to compare the performance of freehand 3D with 4D transducer imaging (group 1). In addition, we studied five patients with thrombus length >3.8 cm to evaluate the performance of freehand 3D imaging in larger clots (group 2). Scanning was performed with routine grayscale, color-flow, and power-Doppler imaging; followed by freehand 3D and 4D transducer volumetric imaging. Postprocessing was performed using the Stradwin software to measure thrombus volume after each scan. Results: The age of patients was 54 ± 13 years (mean ± SD), 73.3% of DVTs were in the upper extremity, and 60% of the patients received anticoagulation. The mean thrombus volume in group 1 measured by freehand 3D and 4D probes was 0.49 ± 0.40 cm 3 and 0.52 ± 0.46 cm 3, respectively, and there was no significant difference between the measurements ( t = −1.57, p = 0.15). Regression analysis demonstrated good agreement between the two imaging modalities ( R 2 = 0.99, regression slope = 1.13, p < 0.001). The freehand 3D technique was also successfully used to quantify thrombus volume (4.71 ± 3.28 cm 3 ) in five patients with DVT >3.8 cm in length (group 2). Conclusions: The described freehand 3D imaging protocol reliably measures thrombus volume in patients with acute DVT when compared with the commercially available 4D transducer. The freehand 3D method has the additional benefit of measuring thrombus volume in DVTs >3.8 cm in length. The method is convenient and can be used in clinical practice.